Mark's Ending in the Digital Age. Issue 1 (2nd November 2021) - Monier, Mina
Abstract : In approaching the classic problem of Mark's ending, it has been assumed that there was no stone left unturned. However, the dawning of the digital age has proven otherwise. As part of the SNSF–funded project MARK16, I have studied the complex evidence of Mark 16's textual transmission to understand the scribal textual decisions. This was followed by electronic transcription of the studied material as part of the digitization process. I will argue, in the first part, that the hitherto neglected paratexts and codicological remarks provide rich evidence on the dynamics of the Endings' reception, conception and later transmission, being inextricably interwoven with patristic interpretation. As a result, I will provide two new witnesses to the Shorter Ending, embedded in a commentary text. In the second part, I will show how transmitting this complex evidence through electronic transcription is another stage in line with earlier scribal experience that problematizes established categories in scholarship.